1979
DOI: 10.1128/jcm.9.2.294-296.1979
|View full text |Cite
|
Sign up to set email alerts
|

Compact anaerobic glove box for hospitals and research laboratories

Abstract: An anaerobic glove box designed for moderate-sized hospitals or research laboratories is described. The compact vinyl and metal enclosure becomes anaerobic rapidly after inflation, requires no vacuum pump, and provides incubator space equivalent to 15 standard anaerobic jars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A number of research areas, such as found in chemistry and biology, need to be conducted in appropriate local due to two main reasons: The first is to protect the researcher from toxic materials and the second is when the materials to be manipulated are moisture or oxygen sensitive. 1,2 A Glove box is a simple apparatus that can solve these problems by coupling a pair of gloves in a sealed compartment which can be filled with an inert gas under at pressures that are slightly higher, lower or equal to atmospheric pressure. Many models of glove boxes are reported in the literature which can be cubic, trapezoid, cylindrical or in a bag-type format.…”
Section: Introductionmentioning
confidence: 99%
“…A number of research areas, such as found in chemistry and biology, need to be conducted in appropriate local due to two main reasons: The first is to protect the researcher from toxic materials and the second is when the materials to be manipulated are moisture or oxygen sensitive. 1,2 A Glove box is a simple apparatus that can solve these problems by coupling a pair of gloves in a sealed compartment which can be filled with an inert gas under at pressures that are slightly higher, lower or equal to atmospheric pressure. Many models of glove boxes are reported in the literature which can be cubic, trapezoid, cylindrical or in a bag-type format.…”
Section: Introductionmentioning
confidence: 99%